Endoscopic dacryocystorhinostomy versus external dacryocystorhinostomy for treatment of primary acquired nasolacrimal duct obstruction - Mohamed Kamel Al Awady; Mohamed Amin El-Morsy; Ahmed Sobhe Abdelaal; Mostafa Osaman Hussein (Wolters Kluwer Medknow Publications, 2021)
Background Dacryocystorhinostomy (DCR) is an operation that creates a lacrimal drainage pathway into the nasal cavity to facilitate drainage of the previously obstructed excreting system. Objective To compare effectiveness and complications of external and endoscopic DCR for treatment of primary acquired [nasolacrimal duct obstruction (NLDO)]. Patients and methods The present study included 60 patients (38 females and 22 males) aged between 18 and 50 years complaining of epiphora owing to NLDO. Patients were subdivided into two groups: group A included 30 (50%) eyes of 25 patients who were subjected to endoscopic DCR, and group B included 30 (50%) eyes of 27 patients who were subjected to external DCR. Results In this study, the right eye was more commonly affected than left eye. The percentage of right eye affection was 53.3% and left eye affection was 33.3%%. Massive intraoperative bleeding in group A was seen in five (16.5%) cases, whereas in group B, massive intraoperative bleeding was noted in nine (29.7%) cases. The difference was statistically nonsignificant (P=0.617). The successful surgical outcome after 6 months was achieved in 28 (92.4%) of 30 patients for the endoscopic DCR and 26 (85.4%) of 30 patients for external DCR surgery. The difference was not statistically significant (P=0.604). Conclusion DCR is the standard treatment for NLDO. It can be performed by external or endoscopic approach. Both these approaches have minimal complications and comparable surgical outcome. However, endoscopic DCR is a safe, minimally invasive effective day-care technique with good aesthetic results.